SUBSTITUSI TEPUNG DAUN MENGKUDU DALAM RANSUM MENINGKATKAN KINERJA AYAM BROILER - Wardiny, Tuty Maria; Azwar Sinar, T Eduard; Zainuddin, Desmayati (LPPM Universitas Terbuka, 2011)
An experiment was conduted to evaluate the effectiveness level of corn substituted by Morinda citrifolia leaf meal in broiler ration. The use of Morinda citrifolia leaf meal substituted for corn in ration is expected to improve feed conversion in broiler chickens and produce chicken meat that safe for consumption and free of chemical antibiotics residues . Completely Randomized Design (CRD) was used to analyze data obtained from this research. One hundred and sixty chicleas (7 days aged) divided into 5 (five) treatments with 4 (four) replications and each replication consisted of 8 (eight) chicleas. Ration of treatments were a negative control diet (R0), 1% Morinda citrifolia leaf meal (R1), 2% Morinda citrifolia leaf meal (R2), 3% Morinda citrifolia leaf meal (R3) and commersial ration (R4). All treatments rations were added a natural feed additive that consist of 0,125% Curcuma and.0,075% Turmeric meal. Measured parameters were feed intake, weight gain, feed conversion ratio, mortality, percentages of carcas and abdominal fat. Results showed that feed consumption, weight gain, and feed conversion ratio were significantly (p <0.05) influenced by treatments. Mortality, percentage of carcas and abdominal fat were not significantly (p >0.05) influenced by ration treatments. Mortality rates in chickens using a ration of treatment was 0%, while using the control diet 0,78% (1 bird). The counclusion showed that the substitution of 1-2% Morinda citrifolia leaf meal in ration has better performance compared to the control diet, with improvement of feed conversion ratio was 7.57 and 9.2% respectively was more efficient than the control diets